An analysis of turkish transport sector in the accession period of european union - Kent, Oya (My University, 2007)
AVRUPA BİRLİĞİ’NE GİRİŞ SÜRECİNDE TÜRK ULAŞTIRMA SEKTÖRÜNÜN ANALİZİ ÖZET Ulaştırma ekonomik aktivitenin tam kalbinde yer almakta ve bütünleşen küresel ekonominin artan talepleriyle birlikte gelişim gösteren uluslararası ticaretin en önemli yapı taşlarından birisini oluşturmaktadır. Aynı zamanda ulaştırma, sürdürülebilir bir kalkınma elde etme sürecinde ağları aracılığıyla ülkeler ve bölgeler arası bütünleşmeye de katkıda bulunur. Günümüz ekonomilerinde ulaştırma maliyetlerinin toplam maliyetler içerisinde önemli bir yer tutmasına bağlı olarak, ülkeler arası rekabette ulaştırmanın önemi artmıştır. Bu çalışma AB ulaştırma politikasının temellerini incelemekte ve oradan hareketle AB’ye katılım öncesi süreçte Türkiye’deki ulaştırma sektörünün durumunu değerlendirmektedir. Çalışma genel olarak bu sektördeki mevzuattaki son gelişmeler üzerinde odaklanmakla birlikte bunun yanında hem AB hem de Türkiye’deki ulaştırma sektörünün bugünkü durumunu ortaya koymaktadır. AN ANALYSIS OF TURKISH TRANSPORT SECTOR IN THE ACCESSION PERIOD OF EUROPEAN UNION

Transportation takes place at the core of economic activity. It is one of the key elements of international trade that develops in accordance with increasing demands of the integrated global economy. It also assists in the integration between countries and regions through its network in the process of getting a sustainable development. In order that transportation costs engage substantially in total costs in economies of today, the significance of transportation in competition among countries has increased. This study analyses the origins of the EU transportation policy and moving from there evaluates the situation of Turkish transportation sector in the pre-accession period to EU. The study mainly focuses on recent legislative developments in this sector and besides displays the current situation in transportation sector both in EU and Turkey.
Keywords: Avrupa Birliği; Ekonomi; Ulaştırma; Ulaştırma Politikası